Satisfaction of Elderly Hearing Aid Users - Kozlowski, Lorena; Ribas, Angela; Almeida, Gleide; Luz, Idalina (International Archives of Otorhinolaryngology, 2017)
Introduction The impact of auditory sensory deprivation in the life of an individual is enormous because it not only affects one's ability to properly understand auditory information, but also the way people relate to their environment and their culture. The monitoring of adult and elderly subjects with hearing loss is intended to minimize the difficulties and handicaps that occur as a consequence of this pathology.Objective To evaluate the level of user satisfaction with hearing aids.Methods A clinical and experimental study involving 91 elderly hearing aid users. We used the questionnaire Satisfaction with Amplification in Daily Life to determine the degree of the satisfaction provided by hearing aids. We evaluated mean global score, subscales, as well as the variables time to use, age, and degree of hearing loss.Results Mean global score was 4.73, the score for Positive Effects 5.45, Negative Factors 3.2, demonstrating that they were satisfied; Services and Costs 5.98: very satisfied ; 3.65 Personal Image: dissatisfied. We observed statistically significant difference for the time of hearing aid use, age, and degree of hearing loss.Conclusion The SADL is a tool, simple and easy to apply and in this study we can demonstrate the high degree of satisfaction with the hearing aids by the majority of the sample collected, increasing with time of use and a greater degree of hearing loss.
Keywords: patient satisfaction; quality of life; hearing aids; hearing Loss